(untitled) (Revista Brasileira Multidisciplinar, 2020)
The present work had as general objective to investigate how the application of coaching can be used as a tool to guide and support the egress of the socio-educational system in the construction of their life project outside crime. For a better treatment of the objectives and better appreciation of this research, it was bibliographic, we sought themes related to socio-education, adolescence, coaching, among others necessary were searched. From the data analysis it was possible to realize that there is little literature on the specific topic, we verified that coaching in socio-education is something new, needing to be more studied and debated. Finally, through the study conducted, it was noticed that socio-education is an area that can be more explored for the use of coaching, mainly in the construction and monitoring of the individual attendance plan where himself plans how it will be all your walk in the socio-educational measure and also how will be their reinsertion in society.